Optimal parameter estimation of MISO system based on fuzzy numbers / Razidah Ismail ... [et al.] - Ismail, Razidah; Ahmad, Tahir; Ahmad, Shamsuddin; Ahmad, Rashdi Shah (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2006)
A great deal of information for many real-world problems arising in multivariable control systems is provided by human experts. Often, the decision parameters of the systems are described verbally through vague, uncertain or imprecise statements. This situation can be taken into account by using fuzzy numbers, which has been proved to be a very useful tool. Thus, this paper discusses the development of a Fuzzy State Space algorithm for optimal parameter estimation in multiple-input single-output (MISO) system based on fuzzy numbers. Briefly, the procedure involved fuzzification of all the input parameters, processing of the fuzzified parameters in the fuzzy environment and defuzzification of the processed data. The optimal input parameters are determined by the Modified OptimizedDefuzzified Value Theorem. As an illustration, this algorithm is applied to a system with three input parameters.